2008
DOI: 10.1007/s00436-008-1059-4
|View full text |Cite
|
Sign up to set email alerts
|

Spread of ticks and tick-borne diseases in Germany due to global warming

Abstract: Tick-transmitted diseases like tick-borne encephalitis and Lyme Borreliosis have been well known in Germany for decades. Global climate changes may influence the emergence and reemergence of diseases. Ongoing research now gives an additional focus on other tick-borne pathogens such as Coxiella burnetii, Rickettsia conorii, Anaplasma phagocytophilum and Babesia spp., the causative agents of Q-fever, Mediterranean spotted fever, Anaplasmosis and Babesiosis, respectively. The epidemiology of these pathogens was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 26 publications
(22 reference statements)
2
28
1
3
Order By: Relevance
“…However, the presence of A. phagocytophilum in I. ricinus ticks (5, 21) and rodents (26) as potential reservoir hosts has been demonstrated. As part of the present study, we showed for the first time that in Germany sheep, roe deer, and red deer were also infected with A. phagocytophilum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of A. phagocytophilum in I. ricinus ticks (5, 21) and rodents (26) as potential reservoir hosts has been demonstrated. As part of the present study, we showed for the first time that in Germany sheep, roe deer, and red deer were also infected with A. phagocytophilum.…”
Section: Discussionmentioning
confidence: 99%
“…C. burnetii has been detected in 140 species of ticks in 12 genera throughout the word (absent in New Zealand), but the role of ticks in Q fever transmission to humans is very small (Parola & Raoult, 2001b;Tissot-Dupont & Raoult, 2008). Recently, none of 862 Dermacentor ticks tested positive for C. burnetii in Germany, and one specimen of Haemaphysalis punctata from 691 questing adult ixodid ticks was positive in Spain (Hartelt et al, 2008;Barandika et al, 2008). Q fever is usually acquired by the ingestion or inhalation of virulent organisms from infected mammals and their products, most frequently goats, sheep, and cats.…”
Section: Q Fevermentioning
confidence: 99%
“…B. microti has been detected in Europe, for example, in the bank vole (Myodes glareolus) (Duh et al 2003, Beck et al 2011, Tadin et al 2012, the common shrew (Sorex araneus) (Bown et al 2011), and the field vole (Microtus agrestis) (Bown et al 2011), which are suggested as reservoir hosts, but also in the yellow-necked mouse (Apodemus flavicollis) (Duh et al 2003, Sinski et al 2006, Beck et al 2011, Tadin et al 2012). In Germany, B. microti has been detected previously in a striped field mouse (Apodemus agrarius) (Silaghi et al 2012) and with a prevalence of 1.6% in rodents of the family Arviculidae (Hartelt et al 2008). Bank voles are most abundant in woodlands, whereas field vole and the common shrew achieve highest density in long grass and scrub (Dickman and Doncaster 1987).…”
mentioning
confidence: 99%